Effects of Covert Audio Coaching on the Attending Behavior of Children With Autism Spectrum Disorder. (September 2019) - Crocco, Christina; Bennett, Kyle D.
The effects of covert audio coaching, a form of performance feedback delivered remotely through a two-way radio and earbud speaker, was examined on the classroom attending behavior of children with autism spectrum disorder (ASD). Four elementary-aged students with ASD participated. This study was conducted in a private, separate day school for students with ASD. Baseline data showed that participants emitted low levels of attending behavior with a degree of variability. During intervention, all participants increased their level of attending behavior and these data were stable. Follow-up data revealed higher levels of attending compared with baseline; however, these data were more variable than what was observed during intervention. These results and implications for future research and practice are discussed.